2005
DOI: 10.1289/ehp.7280
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat Interacts with PCBs to Induce Changes in Lipid Metabolism in Mice Deficient in Low-Density Lipoprotein Receptor

Abstract: There is evidence that dietary fat can modify the cytotoxicity of polychlorinated biphenyls (PCBs) and that coplanar PCBs can induce inflammatory processes critical in the pathology of vascular diseases. To test the hypothesis that the interaction of PCBs with dietary fat is dependent on the type of fat, low-density lipoprotein receptor–deficient (LDL-R−/−) mice were fed diets enriched with either olive oil or corn oil for 4 weeks. Half of the animals from each group were injected with PCB-77. Vascular cell ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 30 publications
4
54
1
Order By: Relevance
“…Furthermore, coplanar PCBs can suppress delta 5 and 6 desaturase activities, thus disrupting the synthesis of fatty acid precursors for eicosanoid metabolism [17]. Our own data from plasma and livers of LDL receptor-deficient mice support the hypothesis that treatment with PCBs can facilitate clearance of linoleic acid from plasma into vascular tissues [18]. Such a change in lipid milieu could exacerbate fatty acid-and/or PCB-induced oxidative stress and a vascular inflammatory response.…”
Section: Introductionsupporting
confidence: 57%
“…Furthermore, coplanar PCBs can suppress delta 5 and 6 desaturase activities, thus disrupting the synthesis of fatty acid precursors for eicosanoid metabolism [17]. Our own data from plasma and livers of LDL receptor-deficient mice support the hypothesis that treatment with PCBs can facilitate clearance of linoleic acid from plasma into vascular tissues [18]. Such a change in lipid milieu could exacerbate fatty acid-and/or PCB-induced oxidative stress and a vascular inflammatory response.…”
Section: Introductionsupporting
confidence: 57%
“…Investigators typically have insufficient biologic information to specify the correct analytic model, often resulting in analytic strategies based on unverified assumptions. For example, research indicates a possible causal effect of PCBs on serum lipid levels (Hennig et al 2005; Langer et al 2003). Additionally, lipid levels have been suggested to affect breast cancer risk (Atalay et al 2004), but their impact on other health end points has received limited attention.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies in workers exposed to the PCB have reported an increased incidence of liver tumors [185][186][187][188] . Some possible mechanisms by which PCB can cause cancer have been assumed: Reactive oxygen species (ROS) is produced through the enzymatic oxidation or autoxidation of PCB; PCB determines the increased expression of genes responsible for inflammation and apoptosis in the liver; and PCB has "toxic" effects on certain genes, such as the loss of part of a chromosome and chromosome breakage [189][190][191][192][193][194][195][196][197][198][199] . ROS are also able to reduce telomerase activity which can determine telomere shortening.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%